Diagnostic and prognostic values of NSCLC patients with or without obstructive pneumonia after sleeve lobectomy - Huang, Yuxia; Zhang, Lan; Zhang, Wentian; Lv, Na; Wang, Tao (Frontiers in Cellular and Infection Microbiology, 2024)
ObjectiveWe aimed to identify the diagnostic value of next-generation sequencing (NGS) of bronchoalveolar lavage fluid (BALF) from patients with non-small-cell lung cancer (NSCLC).MethodsForty patients who were initially diagnosed with pulmonary nodules were enrolled. Frozen section histology was used to identify the NSCLC cell types. NGS of collected BALF samples was used for microbial identification. We compared the bacterial and viral distributions in BALF samples from patients with NSCLC with and without obstructive pneumonia as well as their NSCLC drainage times following surgery.ResultsOf the 29 patients with NSCLC, eight had obstructive pneumonia. Streptococcus pneumoniae, Streptococcus pseudopneumoniae, and Haemophilus parainfluenzae were the top three bacteria present in almost 50% of patients, both with and without obstructive pneumonia. The viral detection rate was higher in the BALF of patients with NSCLC who did not have obstructive pneumonia. However, in patients with NSCLC and drain times of >5 days, the human herpes virus type 7 detection rate was higher following surgery than it was in patients with NSCLC who had drain times of ≤5 days.ConclusionViral imbalance in NSCLC is closely related to the occurrence of obstructive pneumonia and postoperative drainage time.